Regenerative biology and medicine - Stocum, David L. (Elsevier Academic Press, 2006)
The purpose of the book is to bring together in one place the different facets of regenerative biology and medicine while providing the reader with an overview of the basic and clinically-oriented research that is being done. Not only does the content cover a plethora tissues and systems, it also includes information about the developmental plasticity of adult stem cells and the regeneration of appendages. As part of its balanced presentation, Regenerative Biology and Medicine does address the biological/bioethical issues and challanges involved in the new and exciting field of regenerative biology and medicine. *Tissues covered include skin, hair, teeth, cornea, and central neural types *Systems presented are digestive, respiratory, urogenital, musculoskeletal, and cardiovascular *Includes amphibians as powerful research models *Discusses appendage regeneration in amphibians and mammals.